Virtual acoustic environments for comprehensive evaluation of model-based hearing devices *. (25th May 2018) - Grimm, Giso; Luberadzka, Joanna; Hohmann, Volker
Abstract: Objective: Create virtual acoustic environments (VAEs) with interactive dynamic rendering for applications in audiology. Design: A toolbox for creation and rendering of dynamic virtual acoustic environments (TASCAR) that allows direct user interaction was developed for application in hearing aid research and audiology. The software architecture and the simulation methods used to produce VAEs are outlined. Example environments are described and analysed. Conclusion: With the proposed software, a tool for simulation of VAEs is available. A set of VAEs rendered with the proposed software was described.